1995
DOI: 10.1002/ijc.2910620617
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of aldose reductase gene expression in rat primary hepatoma and hepatoma cell lines: Implication in detoxification of cytotoxic aldehydes

Abstract: Aldose reductase and aldehyde reductase are members of the aldo-keto reductase superfamily, and participate in the reduction of a wide range of carbonyl compounds. We have purified aldose reductase from rat lens and raised antiserum against it in rabbits. Immunoblot analyses using this antibody showed that a significant amount of aldose reductase was expressed in cell lines derived from hepatomas while it was negligible in normal hepatocytes. Elevated expression of aldose reductase was also observed in cancero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Because AR exhibits broad specificity for both hydrophilic and hydrophobic aldehydes, it has been suggested that this enzyme may detoxify compounds with an aldehyde moiety and confer resistance to cells against cytotoxicity of toxic compounds. 37 It is noteworthy that the mouse FR-1 mRNA showing the highest sequence homology with the novel HARP gene is high in the newborn but not in the adult liver, and is induced by fibroblast growth factor. 33 Furthermore, recent reports showing the increased expression of AR gene in induced rat hepatoma are in accordance with our finding of HARP mRNA in all tested human HCC samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because AR exhibits broad specificity for both hydrophilic and hydrophobic aldehydes, it has been suggested that this enzyme may detoxify compounds with an aldehyde moiety and confer resistance to cells against cytotoxicity of toxic compounds. 37 It is noteworthy that the mouse FR-1 mRNA showing the highest sequence homology with the novel HARP gene is high in the newborn but not in the adult liver, and is induced by fibroblast growth factor. 33 Furthermore, recent reports showing the increased expression of AR gene in induced rat hepatoma are in accordance with our finding of HARP mRNA in all tested human HCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, recent reports showing the increased expression of AR gene in induced rat hepatoma are in accordance with our finding of HARP mRNA in all tested human HCC samples. [36][37][38] Carbohydrate metabolism is known to play an important role in the liver during embryonic development. Re-expression of AR could be assumed to be a consequence of unbalanced biological functions during tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR as a tumor-associated variant 40 was detected in 60% of HCC. This is comparable with the results of Cao et al 24 ; they found that in the Asian population, 54% of investigated HCC expressed ARL-1 mRNA and 29% expressed AR mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…AKR inducing agents have included ethacrynic acid (9), ethoxyquin (19), 3Ј-methyl-4-dimethyl-aminoazobenzene (20), and N-methyl-N-nitrosourea (21), while spontaneous induction has been observed during the development of hereditary hepatitis leading to hepatocarcinogenesis (6). Hormonal regulation of AKR members has been observed during the estrous cycle (7), in the cell cycle of Leishmania major (22) and due to the effects of basic fibroblast growth factor on astrocytes (8).…”
Section: Resultsmentioning
confidence: 99%